A meta-analysis of lung weight in drowning deaths - Stanikzai, Alexander Helal; Busch, Johannes Rødbro; Banner, Jytte; Wingren, Carl Johan (Forensic Science International, 2025)
Diagnosing drowning as a cause of death remains complex in forensic pathology, demanding integration of autopsy findings, contextual evidence, and case-specific variables. This study systematically reviews literature on lung weights in adult drowning cases, analyzing data from 20 studies to evaluate lung weight as an evidentiary factor in the diagnosis of drowning deaths. Additionally, this study seeks to examine the impact of covariates such as water salinity (freshwater vs. saltwater) and sex differences on lung weight in drownings deaths. Our meta-analysis examines the weighted average mean and median lung weights, comparing 3010 drowning cases with 1494 controls. We observed significantly higher lung weights in drowning cases compared to controls, with an observed mean difference of 243 g (95 % CI: 217 - 263 g, p < 0.001). Differences in lung weight across cases indicate that factors such as water salinity and sex are associated with the weight of the lungs. However, guidelines for how to interpret lung weight in the medico-legal assessment of cause of death in a specific case is still elusive, since the variation in lung weight is relatively large. Recommendations for future research is to include a standardized reporting of lung weight in categories of age, body size and sex, and to include appropriate control groups to improve the accuracy of drowning diagnosis.
Copyright © 2025 The Authors. Published by Elsevier B.V. All rights reserved.
Keywords: Humans; Drowning/diagnosis; Lung/pathology; Organ Size; Salinity; Forensic Pathology; Fresh Water; Seawater; Female